AIE fluorophore with enhanced cellular uptake for tracking esterase-activated release of taurine and ROS scavenging. (28th November 2016) - Wang, Jun; Wu, Yinglong; Zeng, Fang; Huang, Shuailing; Wu, Shuizhu
Abstract : Fluorophores with aggregation-induced emission (AIE) characteristics are attractive and versatile tools for both chemical sensing and biological imaging. Herein, we designed and synthesized a fluorescent light-up system CTPE-Tau with enhanced cellular uptake ability. The system possesses several advantages, such as a large Stokes shift, low cytotoxicity, and good photostability. Also, it has been successfully utilized to track esterase-activated release of taurine and to scavenge intracellular ROS, and shows great potential for trackable visualized therapy.